Interpenetration of chemically identical polymer onto grafted substrates. (15th September 2015) - Lee, Hoyeon; Jo, Seongjun; Hirata, Toyoaki; Yamada, Norifumi L.; Tanaka, Keiji; Kim, Eunkyoung; Ryu, Du Yeol
Abstract: Interpenetrating interfaces between a deuterated polystyrene (dPS) and the grafted substrates with the same chemical identity were characterized using neutron reflectivity (NR) measurements, where the PS-grafted substrates were prepared using a grafting-to approach with hydroxyl end-functionalized polystyrene (PSOH) in a dry brush regime. The characteristic brush thickness ( h ) and grafting density ( σ ) of PS-grafted layers were determined based on the chain length (or molecular weight, M n ) of PSOHs. The experimental interpenetration length ( ξ ) was measured at the interfaces, and the limiting plateau in ξ above which the value was independent of film thickness shifted toward higher values as the M n of PSOH increased. Normalization by the deformed brush thickness ( h d ) of PS-grafted layer after interpenetration revealed that the experimental value of ξ / h d in a short and dense PS-grafted substrate, prepared with a low-molecular-weight PSOH, deviated markedly from the theoretical value, indicating significant additional stretching of the grafted chains to accommodate inter-mixing with the dPS chains. Graphical abstract: Highlights: Interpenetration behavior of chemically identical polymers onto the grafted substrates. Model layer system to examine interpenetrating interfaces in a dry brush regime. Evaluation of the interpenetration length ( ξ ) at the interfaces between a dPS and PS-grafted layers. Effective diffusion of the dPS chains onto a short and dense PS-grafted layer.